Application of Lean Manufacturing Principles to Increase Productivity in SMEs Manufacturers of Baby Clothes - Quiroz Flores, Juan Carlos (2022)
The textile and garment industry is a business area that keeps growing every day, and specifically, the production of baby clothes has shown to be a highly profitable sector. This work's purpose is to evaluate and propose a feasible solution to counter the main problem presented in small businesses that produce baby clothes through knitting, which is low productivity using the Implementation of tools such as MRP, Jidoka, TPM, and work standardization. Additionally, the main contribution of the investigation is developed through Lewin's change model. This model comprises three phases: unfreezing, change, and refreezing. The first is about recognizing every problem the company could have; the second consists of implementing new ideas or work practices; and, lastly, the refreezing focuses on keeping the changes made to have continuous Improvement through support and reinforcement. Finally, to validate the proposed model proposed, Arena software was used, which, through a significant number of runs, managed to achieve the Improvement of productivity by 11.10%; and, in consequence, other indicators related to the main problem also showed better results, such as the decrease of the quantity of the stock out of stock by 22.01% and the increase of the performance of the weaving machine by 14.93%.